Early Childhood’s Independence: The Influence of Daily Routine Activity Videos in Kindergartens - Jojor Renta Maranatha (SEA-CECCEP, 2020)
The research aims to find about the influence of Daily Routine Activity Videos in kindergartens on early childhood’s independence. It employed a quasi-experimental method with the pretest-posttest control group design. Results were assessed by carrying out a study into two groups, experiment and control groups. The experimental group, which got the treatment by using Daily Routine Activity Video and the control group which did not got the treatment or with a classical instruction. The research participants were 26 children (4-5 years old). The research was conducted in Purwakarta, Indonesia. The results show that: (1) The use of Daily Routine Videos in kindergartens had an influence on early childhood’s independence; (2) There was a difference in the independence of early childhood treated with the Daily Routine Activity Videos and those with a conventional instruction. Hence, the independence of early childhood treated with Daily Routine Activity Videos was better than the children taught with a conventional instruction.